(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
In this work, a newmethod for protecting the patient information is introduced in which theinformation is embedded as a watermark in the discrete wavelet transform (DWT)of the medical image using the hospital logo as a reference image. The schemeis blind so that the EHR can be extracted from the medical image without theneed of the original image. Therefore, this proposed technique is useful intelemedicine applications.